`a) x - 24/8 = 8`
`x = 8 + 24/8`
`x = 11`
`b) 76/18 - x × 17/3 = 4/9`
`x × 17/3 = 76/18 - 4/9`
`x × 17/3 = 34/9`
`x = 34/9 : 17/3`
`x = 2/3`
a, X = 8 + 24/8
X = 11
b, X x 17/3 = 76/18 - 4/9
X x 17/3 = 34/9
X = 34/9 : 17/3
X = 2/3
`a) x - 24/8 = 8`
`x = 8 + 24/8`
`x = 11`
`b) 76/18 - x × 17/3 = 4/9`
`x × 17/3 = 76/18 - 4/9`
`x × 17/3 = 34/9`
`x = 34/9 : 17/3`
`x = 2/3`
a, X = 8 + 24/8
X = 11
b, X x 17/3 = 76/18 - 4/9
X x 17/3 = 34/9
X = 34/9 : 17/3
X = 2/3
Tìm x
76/18 - X x 17/3 = 4/9
tìm x
76/18 - X x 17/3 = 4/9
a .(18 – 9 x 2) x (2 + 4 + 6 + 8 + 10)
b.(7 x 8 – 56 ) : (2 + 4 + 6 + 8 + 112)
c. (2 + 125 + 6 + 145 + 112) x (42 – 6 x 7)
d.(12 x 6 – 12 x 4 – 12 x 2) x ( 347 + 125)
e(a x 7 + a x 8 – a x 15) : (1 + 2 + 3 + ........ + 10)
f.58 – 58 x (6 + 54 – 60)
g.32 + 63 x a x ( a x 1 – a : 1) + 32 x 8 + 32
h.(1 + 2 + 3 + 4 + .... + 9) x (21 x 5 – 21 – 4 x21)
i.(9 x 7 + 8 x 9 – 15 x 9) : (1 + 3 + 5 + 7 + ........+ 17 + 19)
k.(2 + 4 + 6 + 8 + ... + 20) x (56 x 3 – 72 : 9 x 21)
Cách làm nào đúng, cách làm nào sai
a) 24 : 6 :2 = 4 : 2 = 2
b) 24 : 6: 2 = 24 : 3 = 8
c) 18 : 3 x 2 = 18 : 6 = 3
d) 18 : 3 x 2 = 6 x 2 = 12
x = 1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 .
x = 2 + 4 + 6 + 8 + 10 + 12 + 14 + 16 + 18 + 20 .
x = 1 + 3 + 5 + 7 + 9 + 11 + 13 + 15 + 17 + 19 .
Tính nhanh:
(18 - 9 x 2 ) x ( 2 + 4 + 6 + 8 + 10)
(18 – 9 x 2) x (2 + 4 + 6 + 8 + 10)
(7 x 8 – 56 ) : (2 + 4 + 6 + 8 + 112 )
(2 + 125 + 6 + 145 + 112) x (42 – 6 x 7)
(12 x 6 – 12 x 4 – 12 x 2) x ( 347 + 125)
(a x 7 + a x 8 – a x 15) : (1 + 2 + 3 + …….. + 10)
58 – 58 x (6 + 54 – 60)
32 + 63 x a x ( a x 1 – a : 1) + 32 x 8 + 32
(1 + 2 + 3 + 4 + …. + 9) x (21 x 5 – 21 – 4 x21)
(9 x 7 + 8 x 9 – 15 x 9) : (1 + 3 + 5 + 7 + ……..+ 17 + 19)
(2 + 4 + 6 + 8 + … + 20) x (56 x 3 – 72 : 9 x 21)
Phiền nêu cách làm luôn nhé, xin cảm ơn
tính nhanh:
a) 9 x 2 : 2
b) 45 : 9 x 9
c) 10 + 12 + 14 + 16 + ... + 80
d) 217 x 45 + 50 x 217 + 207 x 5
e) 3 x 9 + 18 x 2 + 2 x 9 + 9
g) 2006 x (43 x 10 -2 x 43 x 5) + 100
h) 64 x 4+8 x 3 + 8 + 8 + 8
i) 44 x5 +18 x 10 + 20 x 5
k) 3 x 4 + 4 x6 + 9 x 2 + 18
l) 2 x 5 + 5 x 7 + 9 x 3
tìm x
(8x18 - 5x 18 - 18 x 3 ) x x + 2 x x = 8 x 7 +24
A = (a x 7 + a x 8 - a x 15) : (1 + 2 + 3 + ........ + 10)
B = (18 - 9 x 2) x (2 + 4 + 6 + 8 + 10)